Competitiveness Analysis of the Atlantic Department - Fábregas Rodado, Carlos J. (Corporación Universitaria Americana, 2018)
According to studies carried out in the Department of Atlantico by different institutional actors and academia, this has a great opportunity to improve its competitiveness in the global context and the current globalization.But these studies call attention to the different challenges the department must address to achieve these goals: improve the quality of education in schools; create opportunities and social conditions to overcome poverty, focusing public spending and corporate social responsibility in the most vulnerable areas and socio-economic groups; conduct campaigns to raise awareness among citizens of the importance of good use of natural resources and waste generated to achieve sustainable development, promote the articulation of the financial system in the business sector mainly with micro, small and medium enterprises. In addition to this, promote the creation of institutions and research groups linked to the main productive sectors. Given these challenges in the present work, we intend to analyze the competitiveness indicators of the department of Atlantico based on the five pillars proposed by ECLAC, for competitiveness analysis. It is expected to publish these results and their dissemination reaches the entities in charge of making decisions for the improvement and global competitive support of the department.